Implications of partitioning and transmutation in radioactive waste management (Technical reports series (International Atomic Energy Agency) ;, 2004)
Partitioning and transmutation (P&T) is a potential complementary route in the management of spent fuel resulting from the generation of nuclear power. It has the potential to open new avenues for long term waste management by eliminating long term radionuclides and their thermal effects and thus reducing the necessity or capacities of disposal facilities. Recycling and reuse of nuclear material and other transuranic radioisotopes would have positive effects on the sustainability of nuclear energy and reduce proliferation concerns by burning nuclear material and other transuranic radionuclides. This report analyzes, from an international perspective, the current status of P&T, the potential options for its implementation and its impact on waste management programs and strategies